Learning Software Development through Modeling using an Object Oriented Approach with Unified Modeling Language: A Case of an Online Interview System - Ellen Ambakisye Kalinga (Commonwealth of Learning, 2021)
This paper demonstrates the learning of software engineering through modeling using Object-Oriented Analysis and Design approach with Unified Modeling Language. An online interview management system case project to the whole class was used to develop the software requirement specification. Through modelling, the processes to be considered in software development were also elaborated, where it starts with the identification of major or basic processes of the domain of application, followed by the identification of activities to be performed under each basic process and, finally, transforming the activities highlighted in the functional requirements presentation. Modeling was practised by students through group case projects, and students were active, engaging and focusing on the learning process in such a way that more than 85.9% of students had the courage to attempt design questions during university examinations.